2022
DOI: 10.1002/slct.202103765
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active MgP Catalyst for Biodiesel Production and Polyethylene Terephthalate Depolymerization

Abstract: A highly active heterogeneous catalyst was designed and employed for two relevant transesterification reactions. i. e. biodiesel production and depolymerization of polyethylene terephthalate (PET). The material was prepared in the presence of pectin by the co‐precipitation method followed by calcination at 600 °C (MgP). MgP is efficient for biodiesel production, with a yield of ≈99 % in 6 h/65 °C, and with a molar ratio methanol: oil of 21 : 1. The reference material (MgR, prepared in absence of pectin) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The calcination pretreatment was energy intensive; 700 °C for 4 h. A common feature of heterogeneous systems is high operating temperature (200 °C), likely required to ensure PET dissolution and binding to the catalyst surface. Magnesium oxide and magnesium–pectin catalysts have been reported to give >90% DMT yields along with catalyst recyclability. , A multistep but mild preparation of ZnO nanoparticles was reported by Du et al, with use of the nanoparticles demonstrating excellent DMT yields (>95%) after just 15 min, even at 10 g PET loading …”
Section: Poly(ethylene Terephthalate)mentioning
confidence: 99%
See 1 more Smart Citation
“…The calcination pretreatment was energy intensive; 700 °C for 4 h. A common feature of heterogeneous systems is high operating temperature (200 °C), likely required to ensure PET dissolution and binding to the catalyst surface. Magnesium oxide and magnesium–pectin catalysts have been reported to give >90% DMT yields along with catalyst recyclability. , A multistep but mild preparation of ZnO nanoparticles was reported by Du et al, with use of the nanoparticles demonstrating excellent DMT yields (>95%) after just 15 min, even at 10 g PET loading …”
Section: Poly(ethylene Terephthalate)mentioning
confidence: 99%
“…Magnesium oxide and magnesium−pectin catalysts have been reported to give >90% DMT yields along with catalyst recyclability. 162,163 A multistep but mild preparation of ZnO nanoparticles was reported by Du et al, with use of the nanoparticles demonstrating excellent DMT yields (>95%) after just 15 min, even at 10 g PET loading. 164 A combined LCA and material flow analysis compared the impacts of virgin-PET production, methanolysis, hydrolysis, and mechanical recycling.…”
Section: Methanolysismentioning
confidence: 99%
“…Recent efforts demonstrated the possibility to use bio-based catalyst with decent results. Laldinpuii et al demonstrated that bamboo leaf ash use at 200 °C for 2 h allows a decent retrieving monomers yield (78%), 151 and Gangotena et al also used pectin derivatives to obtain an almost full depolymerisation at 160 °C for 4 h. 152 Zeolites can also present nice alternatives to the classical metal-based catalysts, showing similar performances (>90% within 30 min at 200 °C, MgO/NaY catalyst). 153 Ionic liquids also work pretty well in this temperature/time range, 154,155 even focusing originally on fibres waste.…”
Section: Chemical Recycling Of Polyester Fibresmentioning
confidence: 99%
“…34 For example, the demand for DMT has been steadily increasing across various industries, such as packaging, construction and electronics. 35 Therefore, the methanolysis of PET serves as an effective technology to achieve the high-value recycling of PET waste plastics.…”
Section: Introductionmentioning
confidence: 99%